Acute simulated hypoxia and ischemia in cultured C2C12 myotubes : decreased phosphatidylinositol 3-kinase (PI3K)/Akt activity and its consequences for cell survival - Thomas, Mark Peter (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Physiological Sciences))--Stellenbosch University, 2008.